SKELETAL AND DENTAL MATURITY IN FEMALE ADOLESCENTS WITH MENSTRUAL DISORDERS - Smaglyuk, L.V.; Liakhovska, A.V. (World of Medicine and Biology, 2019)
The aim of the study was to determine the skeletal and dental maturity in adolescent females with menstrual disorders and compare with girls without menstrual irregularity. The study enrolled 57 girls, including 32 girls with menstrual disorders (study group) and 25 girls without menstrual irregularity (control group). Their average age was 14.7 ± 0.31 years. Skeletal maturity was determined by CVM method of Hassel and Farman, dental maturity – by Demirjian method. Results and conclusion. The skeletal maturity of the girls of the control group was correspond to the physiological norm and had a significant direct correlation with the chronological age (r = 0.78, p
Keywords: puberty; female adolescent; menstrual disorders; skeletal maturity; dental maturity